Analysis of unintentional injuries in vulnerable populations, Mexico 2018 - Elisa Hidalgo-Solórzano; Ricardo Pérez-Núñez; María del Rosario Valdez-Santiago; Martha Híjar-Medina (Instituto Nacional de Salud Pública, 2019)
Objective. To estimate the prevalence of unintentional injuries (UI) in people residing in localities with <100 000 inhabitants and to analyze its association with different environmental, household and individual characteristics. Materials and methods. Cross-sectional design that analyses the UI component of Ensanut 100k, which is a probabilistic national survey that focused on households beneficiaries of the program Prospera and those with fewer economic capabilities. Prevalence of UI was estimated considering the complex design of the survey. Association with variables of interest was explored using logistic regression analysis. Results. Prevalence of UI was 5.15% (CI95%: 1.43-6.16); probability was higher in male, those living in the region CDMX-EdoMex, and those with hearing and motor disability. Conclusions. Policies directed to prevent UI need to be strengthened to promote health and quality of life amongst individuals, particularly those with social and economic vulnerability, and to reduce the burden that these conditions impose to public health in Mexico.